2017
DOI: 10.18203/2349-3291.ijcp20171732
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impaired glucose tolerance test and diabetes in overweight, obese and apparently healthy school going adolescents

Abstract: Background: Adolescence is a period of transition from childhood to adulthood. It occupies a crucial position in the life of human beings characterized by an exceptionally rapid rate of growth in physical, mental, sexual, and psychological behavior etc. The present study was planned to study the prevalence of impaired glucose tolerance amongst overweight, obese and apparently healthy school going adolescents in the city of Jaipur, Rajasthan.Methods: The study has been conducted in the Department of Pediatrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similar correlation of IGT in different genders was reported in a cross sectional study conducted in Jaipur, which reported the prevalence of pre-diabetes 8% in boys and 6% in girls. 6 The prevalence of IGT was 16 % and 14 % in grade1 and grade-2 obese subjects, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Similar correlation of IGT in different genders was reported in a cross sectional study conducted in Jaipur, which reported the prevalence of pre-diabetes 8% in boys and 6% in girls. 6 The prevalence of IGT was 16 % and 14 % in grade1 and grade-2 obese subjects, respectively.…”
Section: Discussionmentioning
confidence: 92%